ISLAM DAN MASALAH KEMANUSIAAN PERSPEKTIF PENDIDIKAN PEMBEBASAN - Choiron, Ahmad (EDUKASIA, 2017)
ISLAM AND HUMANITY PROBLEMS IN PEDAGOGIC OF FREEDOM PERSPECTIVE. This study is intended to provide an overview of Islam and humanity problems that have recently developed as a result of the era of globalization and the solution of pedagogic of freedom perspective. Mahathir Mohamad said that globalization era becomes the arena of competition in all aspects of human life, whether social, economic, political, cultural, ideological, and defense and security aspects. Therefore, there is often a tendency of great competition and collision between developed and developing countries and even repressions often happen, one of them is the unfairness of rich aristocracy qou status acts abusively against the poor and small groups. For example, the case of dehumanism to the people of Afghanistan, Libya, Iraq, Yemen, Syria and some Muslim countries in Africa is evidence of the loss of justice values. From the beginning, Islam actually condemns the behavior of injustice, Islam is present to defend the oppressed (mustadl'afin) both systematically and sociologically. Asghar Ali Engineer tries to articulate the theology of liberation Islam in education with the aim of defending mustadl'afin groups by giving awareness and equipping them with a very powerful ideological ideology against the oppressors.